(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2015)
At present predictable secret word patterns are subjectto eves dropping, dictionary attacks and shoulder surfing, numerous shoulder surfing unchanged graphical password patterns proposed. At the same time, the utmost publicity techniques used for authentication are textual passwords. A bit of graphical password schemes that are planned in past years. At most of user’s used words-based passwords than pure graphical passwords, hence we have proposed word-based graphical password schemes. Undesirably, none of existing schemes create hybrid digital graphical password system. In this report, we suggest an improved mainly text-based, numerical based shoulder surfing resistant and other approaches like social engineering resistant, eves dropping and dictionary attacks resistant graphical password by applying colors. In the predictable scheme, the operator can robustly, simply and efficiently login system and observe the security, usability and resistance to various attacks of the projected system.